PROBLEMS OF DIPLOMACY IN THE PROCESS OF EURASIAN INTEGRATION - A. A. Durdyyeva (Vestnik MGIMO-Universiteta, 2014)
Nowadays regionalization and integration are key trends in international relations. The creation of alliances and international organizations and the establishment of contractual relations in various spheres have acquired global dimensions. Among such prominent integration groupings as the EU, ASEAN, APEC, NAfTa, MERCOSUR, the African Union and others, one of the most ambitious is the project of the Eurasian Union, which is aimed at the economic, cultural and political integration of states in the CIS area. The evolution of the EAU from idea to the main stages of implementation took quite a lot of time. The modern political initiative proceeding from the leaders of Russia, Kazakhstan and Belarus represents a mature legal form, which actually reflects the historically prevalent tendency of the post-Soviet peoples to associate with each other. The successful functioning of the Customs Union and the Common Economic Space were preconditions to the project of the Eurasian Union. The Union State of Russia and Belarus and Organization of the Collective Security Treaty associations played a particular role in structuring the EAU. Today the establishment of the Union has become one of the defining trends of Russian policy. The basic stages of integration are completed; however, a large number of the economic and political challenges of the future EAU are still to be faced. One of the stumbling blocks is the problem of choosing the model of the future Eurasian diplomacy. The appearance of the chosen model is actually confronted with inevitable and sometimes unforeseen obstacles. The integration experience of other international organizations (primarily in legal, diplomatic and economic spheres) will help to overcome them. In particular, considerable experience has been gained by the European Union. Despite a number of political, cultural and economic constraints, the possibility of transferring the EU diplomatic system to the EAU can't be rejected. The EAU establishment through the legal, economic and political mechanisms used by the EU in elaborating its diplomatic system may lead to a unique system of diplomatic cooperation. The EU experience analysis and the possibility to prevent its mistakes will allow the EAU to make use of the existing integration, political and economic resources more efficiently on its way toward establishment.